Lymphaticovenous anastomosis of the caudal thoracic duct to an intercostal vein: A canine cadaver study - Shriwise, Georgia B.; Loeber, Samantha J.; Hardie, Robert J. (Veterinary surgery, 2021)
Objective To describe a technique for anastomosis of the thoracic duct (TD) to the 11th or 12th intercostal vein (ICV) using a microvascular anastomotic coupler (MAC) in the dog. Study design Cadaveric study. Animals Eight beagles. Methods A right paracostal laparotomy and 10th intercostal thoracotomy were performed in each dog. Mesenteric contrast lymphography was used to identify the TD and its branches on fluoroscopy. The TD and adjacent 11th or 12th ICV were isolated, double ligated, and divided using a surgical microscope. The caudal TD and proximal ICV were anastomosed in an end‐to‐end fashion using a 1.5 mm or 2 mm MAC. Mesenteric lymphography was repeated to document patency of the anastomosis. Results The TD was identified via lymphography in all dogs; five dogs had a single duct, and three dogs had additional branches. The anastomosis was successful in all eight dogs, and flow into the azygos vein without leakage was confirmed via lymphography. Conclusion End‐to‐end anastomosis of the TD to an ICV using a MAC was technically feasible in the canine cadaver. Clinical significance Lymphaticovenous anastomosis combined with TD ligation may have application as a treatment for idiopathic chylothorax. By maintaining the flow of chyle from the abdominal lymphatics to the systemic circulation, this procedure may reduce the stimulus for collateral circulation and persistent flow to the cranial mediastinal lymphatics.